Diagnostic performance of ultrasound versus 99mTc-sestamibi scintigraphy in preoperative depiction and localization of parathyroid adenoma in patients with primary hyperparathyroidism - Gürlüler, Ercüment (The European Research Journal, 2025)
Objectives: To evaluate diagnostic performance of ultrasound (US) and 99mTc-sestamibi scintigraphy (MIBI) in preoperative depiction and localization of parathyroid adenoma in patients with primary hyperparathyroidism (PHPT) Methods: A total of 645 patients (mean age: 52.3 [range; 18-81] years, 72.9% were females) who underwent parathyroidectomy for PHPT due to histopathologically-confirmed adenoma were included in this retrospective cohort study. The accuracy of preoperative US and MIBI in the depiction and localization of parathyroid adenomas was evaluated with respect to intraoperative localization. Results: Preoperative MIBI was more accurate than preoperative US in identifying upper right (6.2% vs. 2.6%) and upper left (7.5% vs. 3.8%) orthotopic adenomas, and ectopic adenomas (1.5% vs. 0.7%). Failure to identify an adenoma was less commonly noted on preoperative MIBI than on preoperative US (26.9% vs. 32.8%). The US mainly failed to diagnose the adenomas located in the upper left (27.4%), lower left (25.9%) and upper right (19.3%) orthotopic sites, while MIBI mainly missed those located in the lower left (36.2%), lower right (24.7%) and upper left (20.1%) orthotopic sites. True-positive depiction rates on the preoperative US (60.4% for ≤250 mg, 80.3% for ≥901 mg) and MIBI (56.7% for ≤250 mg, 86.7% for ≥901 mg) were increased as the parathyroid weight increased. Conclusions: Our findings indicate inconclusive results in the identification of parathyroid adenoma in nearly one-third of cases with both US and MIBI and the side-specific and site-specific variations in their performance. Hence, the combined use of these imaging modalities may be of great clinical value in the precise preoperative depiction and localization of parathyroid adenomas.